Signal transduction - Gomperts, Bastien D. (Academic Press, 2002)
Signal Transduction is a well-illustrated, coherent look at cellular signaling processes. Beginning with the basics, it explains how cells respond to external cues, hormones, growth factors, cytokines, cell surfaces, etc., and then shows how these inputs are integrated and coordinated.